THE SCIENTIFIC AUTHORITY OF ULAMA IN THE ERA OF SOCIAL MEDIA ALGORITHMS AND THE SHIFT IN THE LEGITIMACY OF ISLAMIC FATWAS - Kamil Azka; Azarudin Awang (Yayasan An-Nur Meunara Baro, 2026)
The rise of social media has introduced a new space for the formation and negotiation of religious authority within contemporary Muslim societies. Digital platforms have transformed the ways Islamic knowledge and fatwas are disseminated, accessed, and legitimized, shifting authority from traditional scholarly institutions toward algorithmically amplified religious actors. This transformation raises critical concerns regarding the legitimacy of Islamic fatwas in an era where visibility, popularity, and audience engagement increasingly shape public trust. The growing influence of algorithms challenges long-established models of ulama authority rooted in scholarly competence, methodological rigor, and institutional recognition. This study aims to analyze the shifting dynamics of Islamic scholarly authority in the context of social media and algorithmic governance. It focuses on examining how algorithms influence the circulation of fatwas, redefine patterns of religious legitimacy, and create tensions between scholarly expertise and digital popularity. Employing a qualitative research design with a conceptual–analytical approach, this study relies on systematic literature review and critical discourse analysis of academic publications on Islamic authority, digital religion, and social media published between 2019 and 2026. The findings reveal that social media algorithms play a decisive role in shaping religious visibility and public preference, often privileging simplified, emotionally engaging religious content over methodologically grounded scholarship. This condition produces a structural gap between traditional ulama authority and digitally popular religious figures. The study further highlights adaptive responses by ulama and religious institutions, ranging from strategic digital engagement to ethical resistance. Theoretically, this research contributes to contemporary debates on religious authority and digital mediation. Practically, it underscores the need for integrating digital ethics and media literacy into Islamic scholarship to safeguard the integrity of fatwa production in the algorithmic age.